Pengaruh Filler Mikro Partikel Karbon Tempurung Kelapa (Cmp-Cs) Terhadap Photo Makro Dan Kekuatan Tarik Komposit Polyester - Wahyudyanto, Jayi, Ir. Ngafwan, MT, Agus Yulianto, ST, MT (2016)
This study aims to describe about effect of carbon micro particle-coconut shell (CMP-CS) as filler to the structure of the material (photo macro) and tensile strength of the polyester composite. Composite manufacturing method using a press mold. Composite manufacturing using the variation of the fraction of weight filler carbon micro particle-coconut shell (CMP-CS) 1 %, 3 %, and 6 % with a polyester resin with type Yukalac 157 BQTN-EX. Mixing of the carbon micro particle with resin using stirring method with the rotation speed of 2200 rpm for 7 minutes. Manufacturing of tensile test specimens using a standard ASTM D 638-01. Before to the tensile test, do macros photos to find out arrangement of carbon particles in the composite. The result of the macro photos obtained is the value of distance and diameter carbon micro particles. The average distance to the specimen micro filler composite with carbon particles (FK) 1% is 45 µm, FK 3% is 38,9 µm and FK 6% is 30,6 µm. The higher the weight fraction of carbon, the lower distance of carbon particles. Carbon particle diameter is measured size of 8,48 µm to 29,42 µm. The result of tensile test on specimen obtained the average value of tensile strength (yield) of raw material is 25,37 N/mm2, FK 1% is 27,34 N/mm2, FK 3% is 27,44 and FK 6% is 28,44 N/mm2. While the average value of tensile strain (yield) in the specimen raw material is 0,73%, FK 1% is 0,87%, FK 3% is 0,93% and FK 6% is 0,94%. Discussion of the result of the test result it can be concluded that the provision of carbon micro particles can improve tensile strength and tensile strain polyester composite. Keywords: Filler, Carbon Mirco Particles, Coconut Shell, Polyester, Photo Macro, Tensile Strength